2012
DOI: 10.1007/s10198-012-0424-5
|View full text |Cite
|
Sign up to set email alerts
|

The cost-effectiveness of smoking cessation support delivered by mobile phone text messaging: Txt2stop

Abstract: BackgroundThe txt2stop trial has shown that mobile-phone-based smoking cessation support doubles biochemically validated quitting at 6 months. This study examines the cost-effectiveness of smoking cessation support delivered by mobile phone text messaging.MethodsThe lifetime incremental costs and benefits of adding text-based support to current practice are estimated from a UK NHS perspective using a Markov model. The cost-effectiveness was measured in terms of cost per quitter, cost per life year gained and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
129
0
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 155 publications
(142 citation statements)
references
References 19 publications
11
129
0
2
Order By: Relevance
“…8 Mobile phones provide a broad-reach delivery mechanism for effective, low-cost health behaviour support. [9][10][11] Support via text message is likely to be acceptable to young people and might increase safer sexual health behaviours. Mobile phones are able to provide confidential and non-judgemental support, which is essential for a sexual health intervention.…”
Section: Fundingmentioning
confidence: 99%
“…8 Mobile phones provide a broad-reach delivery mechanism for effective, low-cost health behaviour support. [9][10][11] Support via text message is likely to be acceptable to young people and might increase safer sexual health behaviours. Mobile phones are able to provide confidential and non-judgemental support, which is essential for a sexual health intervention.…”
Section: Fundingmentioning
confidence: 99%
“…A significant part of the intervention was smoking cessation programmes, either pharmacotherapy 4, 5, 36, 37, 38, 40, 41, 48, 50, 51, 53, 55, 56, 57, 58, 59, 60, 61, 62, 63, 64, 65, behavioural therapy 6, 42, 47, 66, 67, 68, 69 or a combination of these 33, 34, 35, 43, 45, 46, 49, 52, 54, 70, 71, 72, 73, 74, 75. Several studies evaluated wider tobacco control interventions 39, 44, 76, 77, 78, 79, 80, 81, 82, 83, 84, 85, 86, 87, 88, whereas five studies included both smoking cessation programmes and tobacco control interventions 89, 90, 91, 92, 93.…”
Section: Resultsmentioning
confidence: 99%
“…In total, 23 of 64 studies reported QALY as their main outcome 5, 35, 38, 40, 41, 47, 48, 49, 56, 58, 59, 61, 62, 63, 65, 69, 70, 76, 78, 81, 86, 88, 94, followed by life years (LY) gained ( n  = nine of 64) 33, 43, 46, 66, 67, 68, 73, 74, 89 or a combination of these ( n  = 12 of 64) 4, 6, 35, 36, 37, 39, 42, 44, 57, 77, 80, 83. Five of 64 studies reported disability adjusted life years (DALY) as their main outcome 60, 82, 90, 91, 92, and only four of 64 (incremental) net benefit 52, 53, 55, 71.…”
Section: Resultsmentioning
confidence: 99%
“…[8][9][10][11][12] mHealth technologies also have the ability to affect the amount of treatment delivered by increasing communication between study staff and participants, providing behavioral strategies, and prompting behavior change. [13] Several reviews [14][15][16][17][18][19] have shown that mHealth interventions can be effective in promoting weight loss.…”
Section: Introductionmentioning
confidence: 99%